Differentiating non-responders from responders in children with moderate and severe asthma exacerbations. (2nd April 2020) - Sneller, Hannah; Carroll, Christopher L.; Welch, Kristin; Sturm, Jesse
Abstract: Objective : Our goal was to assess factors associated with non-response to treatment in children presenting to the Emergency Department (ED) with moderate and severe asthma exacerbations. Methods : A retrospective chart review was completed from 9/2014 to 2/2017 for patients with a discharge diagnosis of asthma exacerbation. The Modified Pulmonary Index Score (MPIS) was used to quantify illness acuity. The rate of change of MPIS per hour was calculated, and differentiated responders from non-responders. After examining a histogram of ΔMPIS/h, a threshold of ΔMPIS/h > 0 was used to define response for duration of ED stay. Children included were >2 years and had initial MPIS > 10. Results : Eight hundred and fifty-two children were included. There were 178 (21%) non-responders and 674 (79%) responders. Non-responders were significantly older (7.0 ± 4.0 versus 5.6 ± 3.2 years; p  < 0.001), but there were no differences in gender, race, ethnicity or insurance status. There was also no statistical difference in time to first albuterol treatment (50 ± 41 versus 43 ± 40 min; p  = 0.05), or in time to corticosteroid (95 ± 75 versus 79 ± 64 min; p  = 0.06). Non-responders were significantly more likely to arrive by ambulance (OR 2.2; 95% CI 1.6–3.2), to be admitted to the hospital (OR 2.7; 95% CI 1.8–4.0), and to be admitted to the ICU (OR 5.0; 95% CI 3.1–8.1). Conclusions : One in five children with exacerbations did not respond to treatment. These children were older and more likely to be admitted. Non-measured factors, possibly genetic, may contribute to response to treatment.